Appunti sui volgarizzamenti francesi della «Chirurgia» di Teodorico Borgognoni (Carte Romanze, 2020)
The paper analyzes the two medieval French versions of Teodorico Borgognoni’s Chirurgia. The article shows that they are two independent translations and highlights some of their features.